Electric Properties of Vegetable Oil-Based Dielectric Liquid and Lifetime Estimation of the Oil-Paper Insulation - Caixin Sun; Jian Li; Xiaohu Li; Grzybowski, S. (2006 IEEE Conference on Electrical Insulation and Dielectric Phenomena, 2006)
This paper presents the electric properties of a type of refined rapeseed oil, which can be used as transformer oil. The lifetime of the rapeseed oil-immersed paper is estimated by performing the step-stress test. Two Weibull parameters are used for statistical analysis of mean lifetime of oil-paper specimen. The mathematic models, the inverse power model, and the exponential model are used to fit test data and to calculate voltage endurance coefficients. As a contrast sample, the step-stress test is also performed on the mineral oil-immersed paper specimen. Analysis results show that the rapeseed oil-immersed paper has longer lifetime than mineral oil-immersed paper.